BUSINESS MANAGEMENT IN THE KNOWLEDGE SOCIETY - Alvarez M., José (2002)
This article deals with an organization's assets, based on knowledge management, which requires an effort aiming to a better and total profit of the intellectual capital. It approaches both competitiveness and innovation aspects, for the emergence of a new industry with interactive multi-media, telecommunications and computer science related to products devolopment.